Promoting leadership and quality improvement through external inspections of management of sepsis in Norwegian hospitals: a focus group study - Jan C Frich; Einar Hovlid; Gunnar Husabø; Gunnar Tschudi Bondevik; Inger Lise Teig (BMJ Open)
Objective Inspections and other forms of external assessment may contribute to positive changes in the health services, but the mechanisms of such change remain unclear. We did a study to explore how external inspections may foster clinical improvement in hospitals.Design Focus group study.Setting Statutory inspections of sepsis treatment in hospital emergency departments in Norway.Participants Clinicians, managers and inspection teams involved with the inspections of sepsis treatment in emergency departments at four different hospitals. Twelve focus group interviews were carried out, with a total of 47 participants.Results Three themes emerged as central for understanding how the inspections could contribute to clinical improvement in the emergency departments: (1) increasing awareness about the need to improve the quality of care by providing data on clinical performance, (2) building acceptance for improvement through professional credibility and focus on clinical practice, and (3) fostering leadership commitment.Conclusion Our findings suggest that the inspections have the potential to enhance hospital management and staff’s understanding of complicated care processes and help strengthen the organisational commitment to bring about systemic quality improvements.